Development of Crowd Control and Tracing for Indoor Facility - Loo, Keng Chuin; Mohamad, Shamsul (Evolution in Electrical and Electronic Engineering, 2022)
The recent spread of a communicable virus-like Covid-19 has already disrupted people’s daily life and even threatened our lives. The challenging problems are maintaining social distance and tracing the patients or people who may contact the patient. This study aims to provide solutions to prevent and detect individuals who may have been exposed to patients. The solutions are divided into three parts: crowd control system, RFID attendance system and trace positioning system. The module prototype with these systems are assembled with an Arduino board, ESP board and some sensor. The purpose of the methods is to limit the number of people, record time with names and maintain social distance. As a result, these systems function and work as expected. The project proved its uses and benefits, but there needed improvement to apply in society. As a recommendation, upgrading the parts and covering the exterior is an important step.